Multilayer microfluidic systems with indium-tin-oxide microelectrodes for studying biological cells. (6th June 2017) - Wu, Hsiang-Chiu; Lyau, Jia-Bo; Lin, Min-Hsuan; Chuang, Yung-Jen; Chen, Hsin
Abstract: Contemporary semiconductor and micromachining technologies have been exploited to develop lab-on-a-chip microsystems, which enable parallel and efficient experiments in molecular and cellular biology. In these microlab systems, microfluidics play an important role for automatic transportation or immobilization of cells and bio-molecules, as well as for separation or mixing of different chemical reagents. However, seldom microlab systems allow both morphology and electrophysiology of biological cells to be studied in situ . This kind of study is important, for example, for understanding how neuronal networks grow in response to environmental stimuli. To fulfill this application need, this paper investigates the possibility of fabricating multi-layer photoresists as microfluidic systems directly above a glass substrate with indium-tin-oxide (ITO) electrodes. The microfluidic channels are designed to guide and trap biological cells on top of ITO electrodes, through which the electrical activities of cells can be recorded or elicited. As both the microfluidic system and ITO electrodes are transparent, the cellular morphology is observable easily during electrophysiological studies. Two fabrication processes are proposed and compared. One defines the structure and curing depth of each photoresist layer simply by controlling the exposure time in lithography, while the other further utilizes a sacrificial layer to defines the structure of the bottom layer. The fabricated microfluidic system is proved bio-compatible and able to trap blood cells or neurons. Therefore, the proposed microsystem will be useful for studying cultured cells efficiently in applications such as drug-screening.